Fanny Kemble papers - Kemble, Fanny, 1809-1893.; Kemble, Fanny, 1809-1893.
Correspondence, chiefly with Joshua Francis Fisher, relating to Kemble's divorce in 1849 from Pierce Butler; legal and financial papers relating to the divorce settlement; two volumes of a journal consisting of material used in Kemble's Journal of a Residence in America (1835) which was critical of American social life and customs; and a manuscript copy of the play "An English Tragedy." Correspondents include Pierce Butler, C.H. Fisher, Theodore Sedgwick, and Samuel Gray Ward.
Actress and author. Full name: Frances Anne Kemble. Married name: Frances Anne Butler.
Collection material in English.
"An English Tragedy" formerly cataloged separately in unk82011587 with call number: PR4839.K2 A67 1838.
Keywords: Butler, Pierce, -- 1807-1867.; Butler, Pierce, -- 1807-1867 -- Correspondence; Fisher, Joshua Francis, -- 1807-1873 -- Correspondence; Fisher, C. H. -- Correspondence; Sedgwick, Theodore, -- 1811-1859 -- Correspondence; Ward, Samuel Gray -- Correspondence; United States -- Social life and customs; Drama; Actresses; Authors